Family perceptions of prematurity, neurodevelopment, and early intervention: a qualitative study - Nathália de Figueiredo Silva; Francelio Silva de Sousa Júnior; Beatriz de Oliveira Silva; Roseany Cavalcante da Silva; Hanna Lettícia Oliveira Lima; Carolina Daniel de Lima-Alvarez; Silvana Alves Pereira (BMC Pediatrics)
Abstract Introduction Given that family involvement is essential for both short- and long-term care of premature infants, it is critical to understand the family's perceptions on prematurity, neurodevelopment, and the need for early intervention. Objective To explore family perceptions on prematurity, neurodevelopment, and early intervention. Methodology This exploratory, descriptive, and qualitative study involved two focus groups and ten semi-structured interviews with family members of premature infants across three neonatal care settings: the Neonatal Intensive Care Unit (NICU), Kangaroo Care Unit, and Follow-up Clinic. The guiding script contained five questions aimed at understanding family perceptions of prematurity and their care for neurodevelopment, ranging from the support resources available during hospitalization to family involvement in intervention programs. Bardin's Content Analysis was employed for data inference and interpretation. Results A limited understanding of prematurity was identified among family members, along with their participation in neurodevelopmental care, highlighting the significance of their role in intervention programs. Families reported feelings of insecurity, particularly in the NICU, indicating a reliance on the care provided by the professional team. The Kangaroo Care Unit proved to be ineffective in fostering family autonomy in post-discharge care, as comments from families in outpatient follow-up suggested a lack of understanding regarding the need for continued care for the development of premature infants. Conclusion The NICU environment appears to hinder parental engagement, leaving parents feeling insecure. The Kangaroo Care Unit was not fully effective in transitioning families to the home environment. Parents in outpatient follow-up exhibited limited understanding of prematurity-related issues.